Trends in Rates of Surgery and Postoperative Mortality Among Patients Receiving Chronic Kidney Replacement Therapy: A Population-based Cohort Study. Issue 6 (2nd December 2022) - Palamuthusingam, Dharmenaan; Hawley, Carmel M.; Pascoe, Elaine M.; Johnson, David W.; Sivalingam, Palvannan; McDonald, Stephen; Boudville, Neil; Jose, Matthew D.; Talaulikar, Girish; Fahim, Magid
Abstract : Objective: To estimate the incidence and postoperative mortality rates of surgery, and variations by age, diabetes, kidney replacement therapy (KRT) modality, and time over a 15-year period. Background: Patients with kidney failure receiving chronic KRT (dialysis or kidney transplantation) have increased risks of postoperative mortality and morbidity. Contemporary data on the incidence and types of surgery these patients undergo are lacking. Methods: This binational population cohort study evaluated all incident and prevalent patients receiving chronic KRT using linked data between Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry and jurisdictional hospital admission datasets between 2000 and 2015. Patients were categorized by their KRT modality (hemodialysis, peritoneal dialysis, home hemodialysis, and kidney transplant) for each calendar year. Incidence rates for overall surgery and subtypes were estimated using Poisson models. Logistic regression was used to estimate 30-day/in-hospital mortality risk. Results: Overall, 46, 497 patients over a median (interquartile range) follow-up of 6.3 years (3.5–10.2 years) underwent 81, 332 surgeries. The median incidence rate of surgery remained stable over this period with a median of 14.9 surgeries per 100 patient-years. Annual incidence rate was higher in older people and those with diabetes mellitus. Patients receiving hemodialysis had a higher incidence rate of surgery compared with kidney transplant recipients (15.8 vs 10.0 surgeries per 100 patient-years, respectively). Overall adjusted postoperative mortality rates decreased by >70% over the study period, and were lowest in kidney transplant recipients (1.7%, 95% confidence interval, 1.4–2.0). Postoperative mortality following emergency surgery was >3-fold higher than elective surgery (8.4% vs 2.3%, respectively). Conclusions: Patients receiving chronic KRT have high rates of surgery and morbidity. Further research into strategies to mitigate perioperative risk remain a priority.